Variations in peak nasal inspiratory flow among healthy students after using saline solutions - Olbrich Neto, Jaime [UNESP]; Olbrich, Sandra Regina Leite Rosa [UNESP]; Mori, Natália Leite Rosa [UNESP]; Oliveira, Ana Elisa de [UNESP]; Corrente, José Eduardo [UNESP] (Elsevier B. V., 2015)
Nasal hygiene with saline solutions has been shown to relieve congestion, reduce the thickening of the mucus and keep nasal cavity clean and moist. Evaluating whether saline solutions improve nasal inspiratory flow among healthy children. Students between 8 and 11 years of age underwent 6 procedures with saline solutions at different concentrations. The peak nasal inspiratory flow was measured before and 30min after each procedure. Statistical analysis was performed by means of t test, analysis of variance, and Tukey's test, considering p<0.05. We evaluated 124 children at all stages. There were differences on the way a same concentration was used. There was no difference between 0.9% saline solution and 3% saline solution by using a syringe. The 3% saline solution had higher averages of peak nasal inspiratory flow, but it was not significantly higher than the 0.9% saline solution. It is important to offer various options to patients.

A higiene nasal com soluções salinas tem sido indicada para aliviar a congestão, reduzir o espessamento do muco e manter a cavidade nasal limpa e úmida. Avaliar se as soluções salinas melhoram o fluxo inspiratório nasal entre crianças sadias. Escolares com idades entre 8 e 11 anos foram submetidos a 6 procedimentos com soluções salinas em diferentes concentrações. O pico de fluxo inspiratório nasal foi medido antes e 30 minutos após cada procedimento. A análise estatística foi realizada por meio de teste t, análise de variância e teste de Tukey, considerando p < 0,05. Foram avaliadas 124 crianças em todas as etapas. Houve diferenças quanto à forma de uso de uma mesma concentração. Não houve diferença entre solução salina a 0,9% e solução salina a 3% por meio de seringa. A solução salina a 3% obteve maiores médias do pico de fluxo inspiratório nasal, porém não foi significativamente superior à solução salina a 0,9%. É importante oferecer diferentes opções aos pacientes.
Variações do pico de fluxo inspiratório nasal entre escolares sadios após o uso de soluções salinas
Keywords: Children; Peak nasal inspiratory flow; Nasal hygiene; Saline; Crianças; Pico de fluxo inspiratório nasal; Higiene nasal; Salina